Approximation of capacities on metric spaces with Lipschitz capacities - Hlushak, I.D. (Carpathian Mathematical Publications, 2014)
For arbitrary capacity on a space with a bounded metric, existence proved and explicit formulae obtained for closest capacities that are Lipschitz continuous with a given Lipschitz constant.